Dampak Implementasi PSAK 73 terhadap Kebijakan Pembayaran Dividen Kas: Peran Moderasi Leverage - Yesi Angraini; Liza Alvia (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study analyzes the impact of PSAK 73 implementation on dividend payout with leverage as a moderating variable in Indonesia Stock Exchange (IDX) retail companies. PSAK 73, effective since January 2020, transformed lease accounting to an on-balance sheet treatment, potentially affecting dividend decisions. Secondary data from 21 retail companies (2020-2024) yielded 105 observations, analyzed using multiple linear regression and moderated regression analysis (MRA). PSAK 73 was proxied by lease liability, dividend payout by Dividend Payout Ratio (DPR), and leverage by Debt to Equity Ratio (DER). Results indicate that PSAK 73 implementation has a significant negative effect on dividend payout (p-value = 0.001), suggesting that increased lease liabilities prompt management to reduce dividends to maintain financial stability. Leverage significantly moderates this relationship (p-value = 0.029 < 0.05), with a positive coefficient that weakens the negative effect of PSAK 73 implementation on cash dividends. Empirically, these findings support Pecking Order and Agency Theories, where companies prioritize internal funding and use lease liabilities to mitigate agency problems. This study contributes to broadening the understanding of the impact of the PSAK 73 lease accounting standard change on cash dividend policies in retail subsector companies listed on the IDX from 2020-2024.